Water use strategies for two dominant tree species in pure and mixed plantations of the semiarid Chinese Loess Plateau. Issue 4 (28th February 2018) - Tang, Yakun; Wu, Xu; Chen, Yunming; Wen, Jie; Xie, Yuli; Lu, Senbao
Abstract: Understanding the water sources and physiological responses to soil moisture pulses for plantation species, particularly in mixed plantations, are essential to assess the water use strategy and vegetation restoration in semiarid regions. We used hydrogen stable isotopes in plant and soil water to determine the potential water sources for Pinus tabuliformis and Hippophae rhamnoides in both pure and mixed plantations in the semiarid Chinese Loess Plateau during the vigorous growing season (June–August) in 2016. Stomatal conductance (gc ), midday leaf water potential (Ψm ) and photosynthetic rate (Pr ) were measured concurrently to analyse the physiological response. The P. tabuliformis in the pure plantation depended largely on shallow and middle soil layers regardless of precipitation amount, permitting this species to maintain stable Ψm at the expense of Pr through stomatal control. In contrast, H. rhamnoides in the pure plantation shifted its water source from shallow to deep soil layers following decreases in precipitation, allowing this species to maintain stable gc and Pr at the expense of Ψm . Thus, P. tabuliformis and H. rhamnoides displayed isohydric and anisohydric behaviour, respectively. Additionally, both species in mixed plantations largely absorbed water from shallow soil layers and shifted to deep soil layers when precipitation decreased. Mixed afforestation significantly reduced ( p  < .05) Pr for P. tabuliformis and Ψm for H. rhamnoides . Although contrasting physiological responses were adopted by these species, the major proportion of water resources were competitively obtained from similar soil depths—indicating that their mixed afforestation requires further investigation.